Revealing twin-induced deformation mechanisms of AZ31 Mg alloy sheet during warm deep drawing - Lei Tian; Lifei Wang; Xinwei Fu; Kunkun Deng; Xiao Wang; Liuwei Zheng; Hongxia Wang; Qiang Zhang; Kwang Seon Shin (Journal of Magnesium and Alloys)
In this work, the {10–12} tensile twins are introduced to improve the drawability of the AZ31 Mg alloy sheet. Concretely, the drawing depth is increased by 32% compared with the as-received sheet at 200 °C. This is because {10–12} tensile twins promote the occurrences of many deformation mechanisms during warm deep drawing, such as slips, detwinning, dynamic recrystallization (DRX) behaviors, etc. Further, based on the different stress states during deep drawing, these mechanisms and their competition relationships, as well as texture evolutions, are systematically studied. Combined with critical resolved shear stress (CRSS) and microstructure evolution, the global Schmid factor (GSF) obtained by quantizing stress states by stress tensor (σ) can accurately predict the activation trend of deformation mechanisms. It is found that the stress states have a reverse influence on the activation trend of the {10–12} twinning and detwinning. The change of stress states affects the competitive relationships between detwinning and DRX, and then affects the process and degree of DRX. The {10–12} tensile twins and large plane strain promote the activation of prismatic slips, and the larger plane strain also deflected the {10–12} twinning lattice. The {10–12} tensile twins and their induced deformation mechanisms can prominently weaken the basal texture and improve the drawability.